2022
DOI: 10.5435/jaaos-d-21-01021
|View full text |Cite
|
Sign up to set email alerts
|

Management of Stress Fractures in Ballet

Abstract: Stress fractures are highly prevalent in ballet dancers and lead to notable time loss from dancing. Nutritional status, body composition, bone mineral density, and rate of increase in activity are among the components that influence risk for stress fractures. Proper evaluation and management of stress fractures is essential including a review of the causative factors involved in each stress injury. The purpose of this article was to summarize current evidence for risk factors involved in dancers' stress fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…(12) Torsion injury resulting in spiral fracture of the femur shaft has been proposed as the most common mechanism of injury. (13)The bulk of the fractures in our dataset were of the same type. If the breech is fixed at the pelvis, excessive traction on the leg during vaginal breech delivery could result in a femoral shaft fracture.…”
Section: Discussionmentioning
confidence: 99%
“…(12) Torsion injury resulting in spiral fracture of the femur shaft has been proposed as the most common mechanism of injury. (13)The bulk of the fractures in our dataset were of the same type. If the breech is fixed at the pelvis, excessive traction on the leg during vaginal breech delivery could result in a femoral shaft fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Although outside the scope of this review, the differential diagnosis for hip pain in ballet dancers should include referred pain from other regions (eg, lumbar pathology and core muscle injury) and metabolic issues (eg, stress reaction/fracture). 14 A recent systematic review of hip/groin injuries in dancers noted that 85% of these injuries were due to overuse rather than a traumatic event. 1 This review will focus on three commonly observed hip pathologies in ballet dancers: impingement, instability, and extra-articular snapping hip syndrome (SHS).…”
Section: Commonly Reported Hip Pathologies and Corresponding Managementmentioning
confidence: 99%
“…The culture of ballet promotes hours of practice at a young age, with professional ballet dancers having logged thousands of hours of training. 14 Ballet classes often range from 1 to 4 hours in length and use repetitive movements, which may contribute to overuse injuries despite good dance mechanics. Unlike many sports that are seasonal, training is often year-round without prolonged periods of rest or seasons of cross-training with other activities.…”
Section: Unique Considerations In Balletmentioning
confidence: 99%
“…Apesar das lesões serem multifatoriais, um estudo em medicina da dança aponta como causas das fraturas por estresse os seguintes fatores: estado nutricional, composição corporal, biomecânica do movimento, carga de treinamento, fatores genéticos e psicológicos. Em relação ao estado nutricional, destacam-se a baixa ingestão energética, deficiência de vitaminas, densidade óssea reduzida, baixo percentual de gordura e comer transtornado como os principais aspectos associados às lesões por estresse (Jotwani et al, 2022).…”
Section: Introductionunclassified